Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/218913
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of Capacitated Supply Chain Networks Including Quality Measures

Abstract: This paper presents (1) a novel capacitated model for supply chain network design which considers manufacturing, distribution, and quality costs (named SCND-COQ model) and (2) five combinatorial optimization methods, based on nonlinear optimization, heuristic, and metaheuristic approaches, which are used to solve realistic instances of practical size. The SCND-COQ model is a mixed-integer nonlinear problem which can be used at a strategic planning level to design a supply chain network that maximizes the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Cost of quality has also direct effect on service cost and indirect effect on Profitability (Aigbavboa & Thwala, 2014). In order to improve quality an organization must take into account the costs associated with achieving quality since the objective of continuous improvement programs is not only to meet customer requirements, but also to do it at the lowest cost (Castillo-Villar, Smith et al 2014). COQ focuses on process improvement and the elimination of all forms of waste.…”
Section: Resultsmentioning
confidence: 99%
“…Cost of quality has also direct effect on service cost and indirect effect on Profitability (Aigbavboa & Thwala, 2014). In order to improve quality an organization must take into account the costs associated with achieving quality since the objective of continuous improvement programs is not only to meet customer requirements, but also to do it at the lowest cost (Castillo-Villar, Smith et al 2014). COQ focuses on process improvement and the elimination of all forms of waste.…”
Section: Resultsmentioning
confidence: 99%
“…Castillo-Villar et al [25][26][27] successfully integrated the cost of poor quality as an analytical expression within the supply chain modeling of manufacturing processes. No work has integrated the quality-related issues and costs within bioenergy supply chains.…”
Section: Integrated Biofuels Supply Chain Modelingmentioning
confidence: 99%
“…Ramudhin et al [38] also introduced a model integrating the Cost of Quality (CoQ) into the supply chain network and found that incorporating COQ in supply chain network design will ensure the lowest overall cost, and reduce the probability of defects of approximately 16%. Castillo-Villar et al [10] developed a mathematical model incorporating CoQ in Supply Chain Network (SCN). They studied the impact of fraction defective and inspection error rate at the manufacturer on total CoQ and quality level.…”
Section: Incorporating Coq In Scndmentioning
confidence: 99%